2021
DOI: 10.1093/mnras/stab1124
|View full text |Cite
|
Sign up to set email alerts
|

KIC 5950759: a high-amplitude δ Sct star with amplitude and frequency modulation near the terminal age main sequence

Abstract: Amongst the intermediate mass pulsating stars known as δ Sct stars is a subset of high-amplitude and predominantly radial-mode pulsators known as high-amplitude δ Sct (HADS) stars. From more than 2000 δ Sct stars observed by the Kepler space mission, only two HADS stars were detected. We investigate the more perplexing of these two HADS stars, KIC 5950759. We study its variability using ground- and space-based photometry, determine its atmospheric parameters from spectroscopy and perform asteroseismic modellin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 98 publications
1
36
0
Order By: Relevance
“…It is not surprising to find frequency variability in δ Sct stars, given their complex behavior with many modes, both radial and nonradial, simultaneously excited. This is illustrated here with two, of many, cases: that of 4 CVn for which Breger et al (2017) analyzed over 800 nights of ground-based photometry obtained over more than 40 yr; and that of KIC 5950759 (Bowman et al 2021) for which 4 yr of Kepler data were analyzed. Breger et al (2017) noted the complexity of the FT of 4 CVn and concentrated their attention on higher amplitude modes.…”
Section: A3 Frequency Variability In Two δ Sct Starsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is not surprising to find frequency variability in δ Sct stars, given their complex behavior with many modes, both radial and nonradial, simultaneously excited. This is illustrated here with two, of many, cases: that of 4 CVn for which Breger et al (2017) analyzed over 800 nights of ground-based photometry obtained over more than 40 yr; and that of KIC 5950759 (Bowman et al 2021) for which 4 yr of Kepler data were analyzed. Breger et al (2017) noted the complexity of the FT of 4 CVn and concentrated their attention on higher amplitude modes.…”
Section: A3 Frequency Variability In Two δ Sct Starsmentioning
confidence: 96%
“…Lares-Martiz et al ( 2020) recognized this and developed a self-consistent method to extract combination frequencies. Bowman et al (2021) showed a plethora of combination frequencies and harmonics in the δ Sct star KIC 5950759, which Lares-Martiz et al ( 2020) used to illustrate their method.…”
Section: Nonlinear Pulsation: Combination Frequencies -Opportunities ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a well-established technique for unravelling nonlinearities in the light curves of oscillating white dwarf stars (e.g., Wu 2001;Zong et al 2016b), and hot B subdwarf stars (e.g., Zong et al 2016a). Yet, it has not received much attention for oscillating MS stars (Lee 2012;Bowman & Kurtz 2014;Kurtz et al 2015;Bowman et al 2016Bowman et al , 2021. In this work, we provide the identification of candidate direct resonances among the extracted oscillation frequencies in the light curves of 38 SPB stars, and test the impact of different iterative prewhitening strategies on the results.…”
Section: Introductionmentioning
confidence: 92%
“…The high-precision photometric data provided by Kepler (e.g., Borucki et al 2010;Koch et al 2010) provides an unprecedented opportunity to explore stellar interiors by using the natural oscillation mode of stars, thus greatly expanding the research field of asteroseismology (e.g., Aerts et al 2010;Chaplin et al 2010;Xue et al 2018;Bowman et al 2021). The ultra-high-precision photometric observations at the μ mag level have significantly advanced our understanding of several types of pulsating variable stars (e.g., Balona et al 2012;Silva Aguirre et al 2015;Stello et al 2022;Szewczuk et al 2022).…”
Section: Introductionmentioning
confidence: 99%